ANALISIS KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD PADA PT PELABUHAN INDONESIA IV (PERSERO) CABANG SAMARINDA - ARAFAH A; PROF. DR. HJ. ENNY ROCHAIDA, M.SI; DR. H. ZAINAL ILMI, SE, MBA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
ABSTRACTION Company Performance Analysis Using the Balanced Scorecard Method of            PT Pelabuhan Indonesia IV (Persero) Samarinda BranchA R A F A HFakultas Ekonomi Dan Bisnis Universitas Mulawarman SamarindaThis study aims to analyze the performance of the company PT Pelabuhan Indonesia IV (Persero) Samarinda Branch with the balanced scorecard method.Data collection is done through primary data and secondary data. Primary data were obtained directly through the distribution of questionnaires to employees and customers of PT Pelabuhan Indonesia IV (Persero) Samarinda Branch and 40 employees and 30 customer respondents were taken as samples. Secondary data obtained through the company's annual report from 2014 - 2018. Data analysis in this study uses the balanced scorecard analysis method.The analysis shows that the company's performance in the financial perspective of ROI, DAR and ROE in the not good category While Sales Growt and CR in the category is not good. For the customer perspective the achievement of customer acquisition and customer profitability in the category is not good but customer retention and customer satisfaction in the good category. In the perspective of internal business processes the achievement AETR in the category is not good but product innovation after-sales service is in the good category and for the perspective of growth and learning of employee retention achievement and employee productivity in the category is not good but employee satisfaction in the good category.Keywords: Balanced Scorecard and Company Performance